Apprentissage du travail dans des situations hybrides en formation professionnelle - Jean-François Métral; Laurent Veillard; Claire Masson (Éducation et Socialisation)
This article illustrates the way in which work can be mobilized in initial vocational training, in hybrid learning situations in school technology workshops. It mobilizes the conceptual framework of vocational didactic to analyze training situations in a workshop for students preparing a diploma in Food Science and Technology in a French agricultural school. It describes the pedagogy deployed by the trainers to teach the work contents to groups of learners, in order to support the connectivity of these contents with the targeted work situations. It provides guidelines for thinking pedagogical engineering of vocational training in work situations.